2017
DOI: 10.3390/antiox6040088
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols as Promising Drugs against Main Breast Cancer Signatures

Abstract: Breast cancer is one of the most common neoplasms worldwide, and in spite of clinical and pharmacological advances, it is still a clinical problem, causing morbidity and mortality. On the one hand, breast cancer shares with other neoplasms some molecular signatures such as an imbalanced redox state, cell cycle alterations, increased proliferation and an inflammatory status. On the other hand, breast cancer shows differential molecular subtypes that determine its prognosis and treatment. These are characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 243 publications
0
44
0
Order By: Relevance
“…Resveratrol (RSV), a natural stilbene found in several plant foods (such as grapes, berries, and peanuts), is one of the most relevant molecules to exert anticarcinogenic effects through many different mechanisms of action, including cell proliferation arrest, initiation and progression inhibition, and/or apoptosis induction against various types of cancer, including BC . Notwithstanding, despite the promising in vitro effects of many polyphenols showing suppressing actions against BC, the clinical evidence is scarce . In this regard, most in vitro studies carried out with polyphenols (and hence RSV) against BC have followed the wrong approach of traditional in vitro assays without considering the polyphenols’ bioavailability, metabolic transformations, and tissue disposition to evaluate and attribute their potential anticancer effects …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol (RSV), a natural stilbene found in several plant foods (such as grapes, berries, and peanuts), is one of the most relevant molecules to exert anticarcinogenic effects through many different mechanisms of action, including cell proliferation arrest, initiation and progression inhibition, and/or apoptosis induction against various types of cancer, including BC . Notwithstanding, despite the promising in vitro effects of many polyphenols showing suppressing actions against BC, the clinical evidence is scarce . In this regard, most in vitro studies carried out with polyphenols (and hence RSV) against BC have followed the wrong approach of traditional in vitro assays without considering the polyphenols’ bioavailability, metabolic transformations, and tissue disposition to evaluate and attribute their potential anticancer effects …”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Notwithstanding, despite the promising in vitro effects of many polyphenols showing suppressing actions against BC, the clinical evidence is scarce. [4,6] In this regard, most in vitro studies carried out with polyphenols (and hence RSV) against BC have followed the wrong approach of traditional in vitro assays without considering the polyphenols' bioavailability, metabolic transformations, and tissue disposition to evaluate and attribute their potential anticancer effects. [7] Animal and human studies have demonstrated low bioavailability and rapid clearance of RSV from the circulation, which is related to its extensive phase-II metabolism catalyzed by enzymes known as transferases, mainly UDP glucuronyl transferases and sulfotransferases (EC number 2.4.1.17 and 2.8.2, respectively), as well as to its microbiota-derived metabolite dihydroresveratrol (DH-RSV).…”
Section: Introductionmentioning
confidence: 99%
“…Jazzara, et al [380] concluded that λ-carrageenan ( Figure 6f) (sulfated galactans found in certain red seaweeds) could be a promising bioactive polymer, showed a remarkable inhibitory effect on MDA-MB-231(triple negative breast cancer cell line) cell migration [381]. Several studies support polyphenols [382][383][384][385][386], flavonoids [387][388][389][390][391][392][393][394][395], fucoidan [396][397][398][399][400][401][402][403][404][405][406][407], lutein/zeaxanthin [408][409][410][411][412], other seaweed alkaloids, peptides, tannins and polysaccharides [413][414][415][416][417][418][419][420][421][422][423][424][425] in breast cancer management ( Figure 7).…”
Section: Camptotheca Acuminate (Xǐ Shù or Happy Tree) Leavesmentioning
confidence: 97%
“…Jazzara et al [170] concluded that λ-carrageenan (sulfated galactans found in certain red seaweeds) could be a promising bioactive polymer, showed a remarkable inhibitory effect on MDA-MB-231(triple negative breast cancer cell line) cell migration [171]. Several studies support polyphenols [172][173][174][175][176], flavonoids [177][178][179][180][181][182][183][184][185][186], fucoidan [159,160,166,[187][188][189][190][191][192][193][194][195], lutein/zeaxanthin [196][197][198][199][200], other seaweed alkaloids, peptides, tannins and polysaccharides [132,164,[201][202][203][204][205][206][207][208][209][210] in breast cancer management. The number of deaths from colorectal cancer in Japan continues to increase [211], it is the third most common diagnosis and second deadliest malignancy for both sexes combined…”
Section: Cancer Prevention and Tumor Controlmentioning
confidence: 99%